INVESTIGATION OF BALANCE AND CORE ENDURANCE IN PATIENTS WITH FIBROMYALGIA SYNDROME - Yentur, S. Baglan; Elbasti, M. S.; Dagdeviren, B.; Cetintas, D. (Elsevier, 2025)
[Abstract Not Available]
Keywords: Physical therapy; Physiotherapy; Qualitative research; and Physical Activity